Arquitetura eclesiástica: perspectivas na Diocese de Osasco no desfecho do século XX - Crispim, Alexandre Douglas (2022)
Through this work we seek to contribute to the studies on the construction of the Catholic sacred space, focusing initially on the origin of the first buildings, their development and transformations that have occurred until the conception of the church as a built building. An initial project of the church starting from the sacraments and sacramentals is presented bearing in mind the requirements that the liturgy makes in relation to the sacred space after the Second Vatican Council, with the aim of enabling the liturgical celebration to flow smoothly with the active participation of the faithful. Therefore, it is an analysis of the situation of the constructions and refurbishments made in the main churches of the current diocese of Osasco at the end of the 20th century, period in which it was being created. The tensions arising from the building process are compared and highlighted according to the cultural reality through the analysis of the main influences on the choices of the forms of such constructions and renovations, especially the need to preserve and enhance the cultural and historical heritage. This study is justified by the changes that occurred in the buildings of the Church in Osasco in relation to the renewal of artistic thought at the Second Vatican Council, including the possibility of opening new horizons for a resumption of the relationship of friendship that artists have always had with the Church, in addition to the rare systematic study on the subject. Initially, it can be assumed that the main influences are related to modern architecture, the formation of priests, migration and the economic crisis. As a conclusion, it is possible to build today nowadays a modern sacred space with noble beauty